STUDYING THE EFFECT OF ROSEMARY EXTRACT ON TYPES OF DERMATOPHYTE THAT EFFECT IN HAIR SCALP - Assist Lecture Abrar Mohammed Qneed Al-Dafay; Assist Lecture Zahraa Ali Hussain; Auha Hameed Salim (European Science Publishing, 2024)
Plants such as Rosmarinus officinalis are used in folk medicine to treat skin problems and infections. investigated the antifungal effects of Rosmarinus officinalis hydroalcoholic extracts against isolates of these three fungi. Dried Rosmarinus officinalis leaves and hydroalcoholic extracts were evaluated against dermatophyte species using the microdilution technique and microscopy. R. officinalis is the most efficient against dermatophytes based on the lowest inhibitory concentration (MIC) and minimal fungicidal concentration (MFC). The mechanisms by which this extract impeded hyphal growth were investigated using scanning electron and fluorescence microscopy. The findings showed a marked inhibition as well as an irregular growth pattern. Through its modification of fungal hyphae and prevention of fungal development, this extract efficiently combats dermatophytes. Therefore, R. officinalis is probably a source of new compounds for the synthesis of antifungal drugs.
Keywords: Plant extract, antifungal and dermatophytosis